Reformation : a radical interpretation of Christianity and the world, 1500-2000 - Fernandez-Armesto, Felipe (New York : Scribner, 1996)
Originally published: Reformation. London: Transworld Publishers, 1996
Includes bibliographical references and index
Keywords: Reformation; Christianity and culture; Religious pluralism -- Christianity